Relationship between physical literacy and cardiorespiratory fitness in children and adolescents: a systematic review and meta-analysis - Jiang, T.; Zhao, G.; Fu, J.; Sun, S.; Chen, R.; Chen, D.; Hu, X.; Li, Y.; Shen, F.; Hong, J.; Hu, H. (Sports Medicine, 2025)
Background: Physical literacy (PL) can positively affect the health of children, adolescents, and adults, and is closely related to cardiorespiratory fitness (CRF). Objective: To perform a systematic review and meta-analysis to examine the relationship between overall physical literacy (PL) and CRF in children and adolescents. Methods: Cross-sectional, cohort and experimental studies on the relationship between PL and CRF in children and adolescents were collected by searching the Web of Science Core Collection, PubMed, EBSCOhost, ScienceDirect, Cochrane Library and China National Knowledge Infrastructure (CNKI) databases. Based on the characteristics of the included literature, PL was divided into physical competence (PC), daily behavior (DB), knowledge and understanding (K&U), and motivation and confidence (M&C). R 4.3.6 was used to analyze the combined effect size of PL and the relationships of the four dimensions with CRF among children and adolescents. Results: A total of 21 articles were included, 42.9% of which were published after 2020, involving a total of 43,352 children and adolescents from 23 countries or regions. The characteristics of the included studies showed that, except for the K&U of children and adolescents aged 13-18 years, the K&U of other age groups and the PL, PC, DB, M&C of all age groups were significantly positively correlated with CRF. Furthermore, the results of male and female samples in all included studies were the same. The results of the meta-analysis indicated that PL (COR = 0.64, 95% CI 0.58, 0.70), PC (COR = 0.74, 95% CI 0.69, 0.79), DB (COR = 0.49, 95% CI 0.40, 0.57), K&U (COR = 0.41, 95% CI 0.23, 0.56), and M&C (COR = 0.45, 95% CI 0.41, 0.49) were significantly positively correlated with CRF. Regarding DB, total physical activity (TPA) was positively correlated with CRF (COR = 0.49, 95% CI = 0.40, 0.57). Moderate to vigorous physical activity (MVPA), vigorous physical activity (VPA) and high physical activity (HPA) were positively correlated with CRF (COR = 0.16, 95% CI 0.09, 0.22; COR = 0.33, 95% CI 0.22, 0.43; COR = 0.38, 95% CI 0.13, 0.58), but light physical activity (LPA) was negatively correlated with CRF (COR = - 0.20, 95% CI - 0.32, 0.06). Conclusion: PL and CRF are positively correlated among children and adolescents, suggesting that the development of physical literacy has a wide range of effects on children and adolescents` cardiopulmonary health and that these effects are not limited by PL and its various dimensions or sex. In addition, to exert the positive effect of daily activities on cardiopulmonary health, the intensity of physical activity should reach a moderate level or above.